2020
DOI: 10.1042/bcj20190877
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of lncRNA 6030408B16RIK prevents ultrafiltration failure in peritoneal dialysis via microRNA-326-3p-mediated WISP2 down-regulation

Abstract: Continuous exposure to peritoneal dialysis (PD) fluid results in peritoneal fibrosis and ultimately causes ultrafiltration failure. Noncoding RNAs, including long noncoding RNAs (lncRNAs) and microRNAs (miRNAs), have been reported to participate in ultrafiltration failure in PD. Therefore, our study aimed to investigate the mechanism of lncRNA 6030408B16RIK in association with miR-326-3p in ultrafiltration failure in PD. Peritoneal tissues were collected from uremic patients with or without PD. A uremic rat mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…50 Cell culture or animal studies have identified lncRNAs such as AV310809 as promoters or AK089579 and 6030408B1RIK as inhibitors of EMT of peritoneal mesothelial cells. [51][52][53] In conjunction with these prior studies, our findings underscore the potential importance of lncRNAs in peritoneal biology and pathobiology.…”
Section: Discussionsupporting
confidence: 75%
“…50 Cell culture or animal studies have identified lncRNAs such as AV310809 as promoters or AK089579 and 6030408B1RIK as inhibitors of EMT of peritoneal mesothelial cells. [51][52][53] In conjunction with these prior studies, our findings underscore the potential importance of lncRNAs in peritoneal biology and pathobiology.…”
Section: Discussionsupporting
confidence: 75%
“…The latest research suggests that lncRNAs have a specific expression profile in fibrotic tissues such as lung, kidney, liver, heart, and peritoneum ( Cao et al, 2013 ; Liu et al, 2015 ). Several researchers revealed that lncRNA-AV310809, 6030408B16RIK, and AK089579 modulate peritoneal EMT ( Wei et al, 2019 ; Zhang et al, 2019 ; Wang Z. et al, 2020 ). However, the specific role and related mechanisms of lncRNA in peritoneal fibrosis remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal dialysis (PD), a type of home dialysis therapy for end-stage renal disease, has been widely used across the world because of its convenience and flexibility [ 1 ], especially in the current COVID-19 pandemic [ 2 ]. However, long-term PD treatment will result in peritoneal fibrosis, a frequent complication due to exposure to glucose peritoneal dialysate [ 3 , 4 ]. Peritoneal fibrosis may affect the function of the peritoneal membrane and ultimately lead to ultrafiltration failure and discontinuation of PD [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%